Dysfunctional amygdala activation and connectivity with the prefrontal cortex in current cocaine users. Issue 10 (28th July 2015) - Crunelle, Cleo L.; Kaag, Anne Marije; van den Munkhof, Hanna E.; Reneman, Liesbeth; Homberg, Judith R.; Sabbe, Bernard; van den Brink, Wim; van Wingen, Guido
Abstract Objectives Stimulant use is associated with increased anxiety and a single administration of dexamphetamine increases amygdala activation to biologically salient stimuli in healthy individuals. Here, we investigate how current cocaine use affects amygdala activity and amygdala connectivity with the prefrontal cortex in response to biologically salient stimuli in an emotional face matching task (EFMT). Experimental design Amygdala activity and amygdala connectivity during the EFMT were assessed in 51 cocaine using males and 32 non‐drug‐using healthy males using functional magnetic resonance imaging (fMRI). Within the cocaine use group, we explored whether amygdala activation was associated with age of first use of cocaine and duration of cocaine use to distinguish between amygdala activation alterations as a cause or a consequence of cocaine use. Principal observations We observed hyperactivity of the amygdala, thalamus, and hippocampus and reduced amygdala connectivity with the anterior cingulate gyrus in response to angry and fearful facial expressions in current cocaine users compared to controls. Increased amygdala activation was independently associated with earlier age of first cocaine use and with longer exposure to cocaine. Conclusions Our findings suggest that amygdala hyperactivity to biologically salient stimuli may represent a risk factor for an early onset of cocaine use and that prolonged cocaine use may further sensitize amygdala activation. High amygdala activation to emotional face processing in current cocaine users may result from low prefrontal control of the amygdala response to such stimuli. Hum Brain Mapp 36:4222–4230, 2015. © 2015 Wiley Periodicals, Inc.